(untitled) (Journal of Dhaka National Medical College & Hospital, 2024)
Background Acute appendicitis remains the common surgical condition and appendicectomy remains the mainstay of treatment for over 130 years. Possibility of non-surgical treatment has been proposed since the middle of the 20th century. An increasing amount of evidence supports the use of antibiotics as conservative treatment instead of surgery for treating patients with uncomplicated acute appendicitis. Objectives To compare conservative treatmentwith appendicectomy in the management of uncomplicated acute appendicitis in adult confirmed by clinical findings and investigations. Methods Ahospital based prospective type of comparative observational study was conducted over a period of three years from 1st January 2020 to31st December 2022 in the Department of Surgery, Dhaka National Medical College Hospital. Total 224 patients of acute appendicitisdiagnosed with history taking, clinical examination, laboratory profile, ultrasonography proven in surgery department of Dhaka National Medical College Hospital were included. Total study population were divided into two groups randomly, one was surgically treated and another one was treated conservatively.Patient treated with conservative treatment received intravenous Ceftriaxone (1 gm/12 hourly) and Metronidazole (500mg/ 8 hourly) for 3 days followed by 7 days of oral Cefixime (400 mg twice daily) and oral metronidazole (500 mg 3 times per day) for 2 days. Patients randomized to the surgical treatment group were assigned to undergo standard open appendicectomy by grid iron incision. The primary end point for the surgical intervention was the successful completion of an appendicectomy and the primary end point for conservative treatment group was discharge from the hospital without the need for surgery. Results In this study, the maximum number of patients 80 (35.71%) was between18-25year age group.Out of 224 cases 126 (56.23%) cases were male and 96 (42.85%) were female. Male and female ratio was 1.3:1. Large numbers of respondents 99 (44.19%) werestudents followed by housewife 48 (21.42%). Leukocyte count (Mean±SD) in surgically treated groupwas 12.7× 109/L and conservative treatment group was12.3× 109/L. Alvarado score was 6-7, which was same in bothgroups. Per-operatively, no collection was seen in right iliac fossa in 86 (76.78%) and serous and purulent collection found in 15 (13.39%) and 11 (9.82%) cases respectively. Only 15 (13.39%) patients had greater omentum present around the appendix, rest 97 (86.60%) patients don’t have greater omentum around the appendix. During operation, 81 (72.32%) appendixes found severely inflamed, 3 (2.67%) were gangrenous and 2 (1.78%) were perforated. Although 8 (6.77%) patients had macroscopically normal appendix. Per-operatively, we found appendiceal lumen was obstructed in only 26 (23.21%) patients. Outcome of the acute appendicitis patient were, median hospitalstay more in conservative treatment group 4.1 days in comparison to surgically treated group 3.4 days. Treatment failed 31 (27.67%) patients were treated by appendicectomy.Among 31 patients, appendix of all 31 (100%) patients were severely inflamed and 25 (80.64%) patients lumen found obstructed with fecalith. Greater omentum found fixed with appendix in 26 (83.87%) patients and serous and purulent collection found in 20 (64.51%) and 11 (35.48%) patients respectively. Readmission required due to recurrent appendicitis occurred in 9 (8.03%) patients in conservative treatment group, who was then treated by appendicectomy, where surgically treated group required no readmission. One third of recurrences appeared within 30 days and two-thirds between 3 and 6 months after hospital discharge. Surgical site infection occurred in 29 (25.89%) patients. Treatment efficacy was 72.32% for conservative treatment. Conclusions The current evidence does not support the routine use of antibiotics as the mainstay of treatment of uncomplicated acute appendicitis because of recurrence and appendicectomy remains the current gold standard. J. Dhaka National Med. Coll. Hos. 2024; 30 (02): 07-14